STRATEGI INDONESIA DALAM MEMPROMOSIKAN PARIWISATA MELALUI ARABIAN TRAVEL MARKET TAHUN 2021 - 2024 - Hartono, Satrio Bayu Tri; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Indonesia actively utilized the Arabian Travel Market (ATM) Dubai from 2021 to 2024 as a strategic platform to promote its tourism sector in the Middle East and international markets. This initiative, led by the Ministry of Tourism and Creative Economy (Kemenparekraf), aimed to revitalize tourism after the COVID-19 pandemic, increase tourist arrivals from the Middle East, and boost national foreign exchange. This article seeks to explore Indonesia’s strategy in promoting tourism through ATM during the 2021–2024 period. This qualitative study employs the theory of public diplomacy and uses literature review as the main data collection method. The findings reveal that Indonesia implemented varied strategies each year: a hybrid format in 2021; business-to-business (B2B) meetings in 2022; the promotion of super-priority destinations under the “Visit Indonesia Year 2023” campaign; and a 2024 collaboration with the DKI Jakarta Provincial Government to promote Jakarta. These efforts demonstrated that participation in ATM has positively contributed to increasing tourist visits and enhancing Indonesia's foreign exchange earnings. Keywords: Arabian Travel Market, Tourism Promotion, Indonesian Strategy.